Getting the EU ready for the next pandemic. (Research'eu results magazine)
For 18 months, the PANDEM project has been preparing recommendations to help the EU face a potential pandemic. Armed with its planning tool and other project outcomes, the team has identified research priorities and innovations needed to strengthen preparedness for pandemics.